A Contribution to the Study of the History of the Church of St. George in Rečani - Stevanović, Bojana M. (Collection of Papers of the Faculty of Philosophy in Priština, 2026)
This paper deals with the history of the Church of St. George in the village of Rečani near Suva Reka, one of the significant, now completely destroyed medieval monuments of Serbian cultural heritage in Kosovo and Metohija. The paper provides an overview of the earliest mentions of Rečani in Dušan’s charter to the Monastery of the Holy Archangels and points to different interpretations of its dating, of which the time around 1348 is most commonly accepted. However, there is no certain evidence that the church already existed at that time. The reliable period in which the church had already been built is established based on a tombstone inscription found in its interior, which records the death of a certain duke on December 23, 1370. An analysis of both the inscription and the burial practices pertaining to ktitors (founders) in churches they commissioned suggests the assumption that this duke was the ktitor of the Rečani church, although the term ‘ktitor’ was not preserved in the inscription. After the 14th century, there are almost no written traces of the church until the 19th century, when travel writers and researchers, such as Ivan S. Yastrebov and Panta Srećković, note that the church was severely damaged, neglected, and exposed to decay. During this period, it is also mentioned that the local Albanian population prevented renovation attempts. The presence of a fire that the church was set on at some point was established based on coloristic changes in the frescoes, but the cause and the time of the fire remain unknown. During the 20th century, attempts were made to repair the structure. The first works were carried out in 1926, while systematic conservation research and restoration were performed between 1955 and 1961. In 1961, the church was placed under state protection as a cultural monument. In the concluding part of the paper, reference is made to the tragic fate of the church after 1999. Although under the protection of international forces, the church was first burned and then blown up with mines in June 1999, thereby irreversibly destroyed. Attention is drawn to contemporary attempts to erase the historical context through inadequate presentation of data about the monument in the institutions of the so-called Republic of Kosovo, thus creating a distorted picture of its past and significance.